COVID-19 mortality amongst the immunosuppresed - Moreno-Torres, Víctor; Martínez-Urbistondo, María; Calderón-Parra, Jorge; de Mendoza, Carmen; Soriano, Vicente (Journal of Infection, 2025)
[Resumen no disponible]
Keywords: COVID-19; mortality; immunosuppresed